Day of vengeance - Dams, Jeanne M. (Dams, Jeanne M. Dorothy Martin mysteries., 2014)
Dorothy Martin's husband, Alan Nesbitt, is heavily involved in the complex and lengthy process of choosing a new bishop for Sherebury Cathedral when one of the candidates is found murdered in his own church.